Efficacy of adjuvant chemotherapy for small bowel adenocarcinoma: A propensity score–matched analysis. Issue 5 (30th December 2015) - Ecker, Brett L.; McMillan, Matthew T.; Datta, Jashodeep; Mamtani, Ronac; Giantonio, Bruce J.; Dempsey, Daniel T.; Fraker, Douglas L.; Drebin, Jeffrey A.; Karakousis, Giorgos C.; Roses, Robert E.
Abstract : BACKGROUND: The role of adjuvant chemotherapy (AC) in the treatment of small bowel adenocarcinoma is poorly defined. Previous analyses have been limited by small sample sizes and have failed to demonstrate a survival advantage. METHODS: Patients with resected small bowel adenocarcinoma (American Joint Committee on Cancer [AJCC] pathologic stage I‐III) who were receiving AC (n = 1674) or surgery alone (SA; n = 3072) were identified in the NCDB (1998‐2011). Cox regression identified covariates associated with overall survival (OS). AC and SA cohorts were matched (1:1) by propensity scores based on the likelihood of receiving AC or the survival hazard from Cox modeling. OS was compared with Kaplan‐Meier estimates. RESULTS: The omission of AC conferred an increased risk of death (hazard ratio, 1.36; 95% confidence interval, 1.24‐1.50; P < .001). After propensity score matching, there was a nonsignificant trend toward improved OS with AC in AJCC stage I patients (158.8 vs 110.7 months; P = .226) and AJCC stage II patients (104.0 vs 79.6 months; P = .185), including the subset with a T4 tumor classification (64.0 vs 47.4 months; P = .130) or a positive resection margin (44.4 vs 31.0 months; P = .333). Median OS was superior for patients with AJCC stage III disease who were receiving AC versus SA (42.4 vs 26.1 months; P < .001). CONCLUSIONS: These data support the use of AC for resected stage III small bowel adenocarcinoma. The trend toward improved OS for patients without nodal metastasis, including those who have T4 tumors or have undergone positive‐margin resection, may justify the use of AC in select patients with earlier stage disease. Cancer 2016;122:693–701. © 2015 American Cancer Society . Abstract : Small bowel adenocarcinoma is a rare gastrointestinal malignancy, and evidence‐based guidelines for the use of adjuvant chemotherapy after surgical resection have previously been drawn from single‐center, retrospective studies, which have not been sufficiently powered to detect a survival benefit. In a propensity score–matched analysis of patients with resected American Joint Committee on Cancer (AJCC) stage I to III small bowel adenocarcinoma identified in the National Cancer Data Base (a population‐based registry), adjuvant chemotherapy demonstrates a significant survival advantage for AJCC stage III patients, regardless of the tumor location. Nonsignificant improvements in survival are observed for AJCC stage I and II patients, including a subset of patients with a T4 tumor classification or a positive resection margin.